Seasonal fluctuation of nematodes trophic groups in the ecotonal forest of cypress (Austrocedrus chilensis) in Argentina - Gobbi, Miriam E.; Brugni, Norma (Bosque (Valdivia), 1996)
The seasonal fluctuation of nematode trophic groups associated with Austrocedrus chilensis forest in the east border of its distribution in the Andean-Patagonian forest (Argentina) was studied. Both soil depth and time of the year were considered as variables. The abundance of nematodes did not vary significantly through the year. The time of the year can be influencing in different ways both each trophic group and the species they compromise . Each trophic group responds to soil depth in a particular way. The highest population levels were found in plantparasitic, followed by omnivorous and microbivorous with very similar density, fungivorous, and very scarse predatious nematodes.